Analysis of Green Bonds - Tobias Friedrich Fauß (Junior Management Science (JUMS), 2022)
Issuing its first green federal security in 2020, Germany pioneered a unique twin bond concept to address potential liquidity risks compared to their conventional counterparts. A switch mechanism between green and conventional bonds was introduced that allows debt-neutral sale-and-purchase (switch) transactions by the issuing authority. The main goal of this dissertation is to provide a theoretical model that is capable to explain the effects of this twin bond concept on the pricing of green bonds. For this purpose, a stochastic liquidity premium following a Vasicek (1977) process, a constant green premium and a switch option, which is executed when the green bond price falls below the price of its conventional twin bond, are assumed. The model results confirm that this twin bond concept is a viable solution to mitigate illiquidity-induced costs for the green bonds. The main learning from the model is a potential positive value of the switch option before its execution. This implies that issuers adopting this concept could benefit from lower costs of capital compared to ordinary green bonds without a switch mechanism. For investors holding the green instruments, this implies a reduced exposure to liquidity risks.
Keywords: 650; Green bonds; German twin bonds; green premium; liquidity premium; switch transactions